Analisa Kelayakan Parameter Kualitas Kimia Air di Perairan Pantai Sorong - Ahmad Yani (Jurnal Airaha, 2015)
Sorong coastal waters with diverse human activities is changes water quality. The environmental quality of coastal waters in Sorong is measurement of chemical water quality parameters. This study aims to determine the chemical water quality coastal waters in worthiness standards for fisheries activity. The measurement was November 2013 to January 2014 in located of coastal waters Sorong-West Papua. Analysis by descriptive and tabular form at each observation station Based on the measurements obtained at station. The measurements has be levels of dissolved Oxygen (02), free Carbon-dioksid, (pH), Ammonia, Nitrate, Orthophosphate, Biological Oxygen Demand (BOD5), and Dissolved Organic Matter (BOT) in coastal waters Sorong in reasonable range for fisheries and be tolerated by aquatic organisms.